2016
DOI: 10.1016/j.jaac.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Behavioral Inhibition Predicts Cortical Thickness in Adulthood

Abstract: Objective Behavioral inhibition (BI) during early childhood predicts risk for anxiety disorders and altered cognitive control in adolescence. Although BI has been linked to variation in brain function through adulthood, few studies have examined relations between early childhood BI and adult brain structure. Method The relation between early childhood BI and cortical thickness in adulthood was examined in a cohort of individuals followed since early childhood (N=53, mean age 20.5 years). Analyses tested whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 62 publications
1
22
1
1
Order By: Relevance
“…Previous authors have described selective increases in DMN rs‐fc as reflecting an “internal shift” that may be a feature of highly shy individuals (Taber‐Thomas et al., ). In contrast to the current results, other studies have reported shyness‐related variation in functional connectivity (Roy et al., ; Taber‐Thomas et al., ), task‐related activity (Clauss et al., ; Guyer et al., , ), and structure (Schwartz et al., ; Sylvester et al., ) in networks beyond the DMN. The most likely explanation for this discrepancy is the specific developmental period of subjects in the different studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous authors have described selective increases in DMN rs‐fc as reflecting an “internal shift” that may be a feature of highly shy individuals (Taber‐Thomas et al., ). In contrast to the current results, other studies have reported shyness‐related variation in functional connectivity (Roy et al., ; Taber‐Thomas et al., ), task‐related activity (Clauss et al., ; Guyer et al., , ), and structure (Schwartz et al., ; Sylvester et al., ) in networks beyond the DMN. The most likely explanation for this discrepancy is the specific developmental period of subjects in the different studies.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the most consistently reported findings has been increased right lateralized brain activity, as measured with electroencephalography, in response to novelty in infants and older children with high versus low behavioral inhibition (Fox et al, 2005). Additional consistently described brain differences in children with high versus low shyness include increased activity in the amygdala to emotionally evocative faces (P erez-Edgar et al, 2007;Schwartz, Wright, Shin, Kagan, & Rauch, 2003); alterations in activity in the nucleus accumbens, striatum, and other subcortical areas during reward processing (Guyer et al, 2006(Guyer et al, , 2014; and structural and functional alterations in brain regions involved in directing attention and cognitive control, such as the FPN, SN, and VAN networks described earlier (Guyer et al, 2015;Jarcho, Fox, Pine, Etkin, et al, 2013;Sylvester et al, 2016). Cross-sectional studies using rs-fc have indicated that shyness or behavioral inhibition is associated with variation of connectivity of the amygdala as well as regions within the DMN, SN, FPN, VAN, and somatosensory networks (Clauss, Benningfield, Rao, & Blackford, 2016;Rogers et al, 2017;Roy et al, 2014;Sylvester et al, 2017;Taber-Thomas, Morales, Hillary, & P erez-Edgar, 2016).…”
mentioning
confidence: 88%
“…To date, studies examining brain structure in adults who were high-BI children reported thinner left OFC and thicker right vmPFC (Schwartz et al, 2010), larger amygdala and caudate volumes , and thinner dACC (Sylvester et al, 2016) in adulthood. In contrast to regional analyses, the prefrontal cortex vertex wise analysis did not detect any regions surviving multiple comparison correction.…”
Section: Cortical Volume Exploratory Analysesmentioning
confidence: 99%
“…In tandem, prefrontal areas such as the orbitofrontal cortex (OFC), ventrolateral-(vlPFC), and dorsolateral-prefrontal (dlPFC) cortices may engage in subsequent cognitive control and emotion modulation (Freitas-Ferrari et al, 2010;Taylor & Whalen, 2015). This gap is particularly important as structural variations may be evident early in development and color subsequent variation in function (Schwartz et al, 2010;Sylvester et al, 2016). However, relatively few studies have examined neural structures and almost exclusively in clinically anxious adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation